Pengaruh Self-Efficacy Terhadap Kemandirian Belajar dan Kemampuan Komunikasi Matematis Siswa SMP - Nafis, Afinta Wardatin; Zawawi, Irwani (Postulat : Jurnal Inovasi Pendidikan Matematika, 2025)
This research is a correlational study with a quantitative approach which aims to determine the influence of self-efficacy on the self-regulated learning and mathematical communication abilities of class VII middle school students. The data analysis used is Structural Equation Modeling (SEM) using AMOS 23. The results of this research show that: (1) There is a positive and significant influence between self-efficacy and student self-regulated learning and C.R. scores. 6.942≥1.967 with a significance level of 0.000≤0.05. (2) There is an influence between self-efficacy and students' mathematical communication skills and C.R. scores. amounting to 2,851≥1,967 with a significance level of 0.004≤0.05. (2) There is a positive and significant influence between self-regulated learning and students' mathematical communication skills and C.R. scores. amounting to 2,752≥1,967 with a significance level of 0.006≤0.05. (4) Because all variables directly influence each other, this research did not find any intervening variables or intermediary variables.